2021
DOI: 10.1002/cctc.202100599
|View full text |Cite
|
Sign up to set email alerts
|

A Cationic Ru(II) Complex Intercalated into Zirconium Phosphate Layers Catalyzes Selective Hydrogenation via Heterolytic Hydrogen Activation

Abstract: Catalytic hydrogenations constitute economic and clean transformations to produce pharmaceutical and a multitude of fine chemicals in chemical industry. Herein, we report a cationic Ru(II) complex intercalated into zirconium phosphate (ZrP) layers that enables the efficient catalytic conversion of furfural and other biomass-derived carbonyl compounds into the corresponding alcohols through selective hydrogenation of C=O group. The ZrP layers acted not only as a support for the Ru-complex, but also as the new l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Besides, the peak of Ru 3p 3/2 around 462.3 eV is attributed to Ru 2+ species, confirming that the Ru center maintained its Ru 2+ state after being incorporated into the POM framework (Figure 2d). 60 The X-ray adsorption fine structure (XAFS) is performed to provide more detailed information on the valence state and chemical environment of Ru sites. XANES spectra of the model compounds (Ru foil, RuO 2 ) as well as K-SiWRu and TOMA-SiWRu samples are shown in Figure 3a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Besides, the peak of Ru 3p 3/2 around 462.3 eV is attributed to Ru 2+ species, confirming that the Ru center maintained its Ru 2+ state after being incorporated into the POM framework (Figure 2d). 60 The X-ray adsorption fine structure (XAFS) is performed to provide more detailed information on the valence state and chemical environment of Ru sites. XANES spectra of the model compounds (Ru foil, RuO 2 ) as well as K-SiWRu and TOMA-SiWRu samples are shown in Figure 3a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In our previous work, it has been demonstrated that the substitution of Ru−Cl coordination bond by Ru−O coordination could promote heterolytic hydrogen activation. 63 Therefore, for the present catalytic system, the in situ formed Ru−OAc complex might also facilitate the dissociation of hydrogen into H δ+ and H δ− , which tended to hydrogenate polar unsaturated C�O group (Table S2, entries 9 and 11), enabling the hydrogenation of polar unsaturated carbonyl bond. 76,78 Usually, ancillary ligands like basic bisphosphine and diamine (en) ligands were needed to stabilize the transition state metal center after the hydride transfer step.…”
Section: Industrial and Engineeringmentioning
confidence: 93%
“…Notably, The Ru−O bond of the Ru−OAc complex could promote the heterolytic cleavage of H 2 (species II) according to our and other group studies. 63,78 The resulting H δ− and H δ+ interacted with the Ru center and the − OAc anion, respectively (species III). Then the hydride attacked the C δ+ of C�O, and − OAc was coordinated to the Ru center to stabilize the H δ+ species (species IV).…”
Section: Industrial and Engineeringmentioning
confidence: 99%
See 2 more Smart Citations